Sosialisasi Pengenalan Dasar Teknologi Jaringan sebagai Pengetahuan Dasar dalam Bisnis Wifi - Muhammad Innuddin; Andi Sofyan Anas; Dedi Febry Rachman; Suryati; Phyta Rahima (Insan Kreasi Media, 2024)
This socialization or training packaged as a Community Service Activity is motivated by the community's lack of understanding regarding the WiFi network when it wants to be developed into a business by the community itself. Based on the results of the service team's evaluation using pre-tests, it was found that people still did not understand what was needed and the function of each device, so for this problem the service team offered a solution in the form of training on WiFi networks. In this training the service team divided it into two sessions, namely a theory session and a field practice session. In this service process, the service team uses the planning, do, check and act (PDCA) method. This method has 4 stages, namely planning, do, check and act. The implementation process went smoothly according to plan and obtained satisfactory results. The evaluation results prove this by providing a post-test after the training and these results show that the public's understanding of WiFi networks has improved for the better.